2020
DOI: 10.1080/19490976.2020.1756150
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic diversity in infant gut microbiota is apparent before the introduction of complementary diets

Abstract: The human gut microbiota develops soon after birth and can acquire inter-individual variation upon exposure to intrinsic and environmental cues. However, inter-individual variation has not been comprehensively assessed in a multi-ethnic study. We studied a longitudinal birth cohort of 106 infants of three Asian ethnicities (Chinese, Malay, and Indian) that resided in the same geographical location (Singapore). Specific and temporal influences of ethnicity, mode of delivery, breastfeeding status, gestational ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 59 publications
4
36
0
Order By: Relevance
“…Self-identified race/ethnicity (SIRE) provides a useful alternative, as it integrates the broader national or cultural tradition of a given social group and is closely tied to both dietary intake and genetic ancestry. Associations between the gut microbiota and ethnicity have been reported in China [10], the Netherlands [11], Singapore [12], and the United States [13, 14]. In contrast, a recent study of Asian immigrants suggested that once an individual relocates to a new country, the microbiota rapidly assumes the structure of the country of residence [3].…”
Section: Introductionmentioning
confidence: 99%
“…Self-identified race/ethnicity (SIRE) provides a useful alternative, as it integrates the broader national or cultural tradition of a given social group and is closely tied to both dietary intake and genetic ancestry. Associations between the gut microbiota and ethnicity have been reported in China [10], the Netherlands [11], Singapore [12], and the United States [13, 14]. In contrast, a recent study of Asian immigrants suggested that once an individual relocates to a new country, the microbiota rapidly assumes the structure of the country of residence [3].…”
Section: Introductionmentioning
confidence: 99%
“…Subdoligranulum , a genus found in nearly all our piglets, has been observed in breast milk microbiomes [42]. In humans, breastfeeding is a source of early infant gut microbes [43], and is a significant predictor of early childhood gut microbiota [44] and immunity [45]. Parity has been shown to affect the lipid and protein content in human breast milk [46], as well as the microbiota composition of cow colostrum [47].…”
Section: Discussionmentioning
confidence: 99%
“…Self-identi ed race/ethnicity (SIRE) provides a useful alternative, as it integrates the broader national or cultural tradition of a given social group and is closely tied to both dietary intake and genetic ancestry. Associations between the gut microbiota and ethnicity have been reported in China [10], the Netherlands [11], Singapore [12], and the United States [13,14]. In contrast, a recent study of Asian immigrants suggested that once an individual relocates to a new country, the microbiota rapidly assumes the structure of the country of residence [3].…”
Section: Introductionmentioning
confidence: 99%